Characterization of cleaners accidents in the Portuguese service sector - Cabeças, José Miquel (2008)
This paper characterizes work accidents at Portuguese industrial cleaning companies, operating in the service sector, through the application of ESAW methodology. Data was codified based on the analysis of 748 accident claims to insurance companies (number of days lost 1 working day) in 3 large industrial cleaning companies for the period 2001-2003. Slipping and falling in the same level was the main deviation from the normal working process in the moment of the accident (in 25% of the accidents); uncoordinated movements was the second cause of accidents (14%); falls of persons to a lower level was the third cause of accidents (~10%), including falls from stairs (~7%) and falls from ladders and mobile ladders (~2%); globally, body movement under or with physical stress, including lifting, carrying, putting down, bending down, twisting, turning, trading badly, twisting leg or ankle and slipping without falling, were the cause in 17% of the accidents. Lower limbs were injured in ~25% of the accidents, hand and fingers in ~14%, the eye in ~4% and the back in ~9% of the accidents. An incidence rate of 3,580 accidents/100,000 employees was found to the sector (2003 data).